Bone and Joint Infections. Issue 8 (August 2017) - Saavedra-Lozano, Jesús; Falup-Pecurariu, Oana; Faust, Saul N.; Girschick, Hermann; Hartwig, Nico; Kaplan, Sheldon; Lorrot, Mathie; Mantadakis, Elpis; Peltola, Heikki; Rojo, Pablo; Zaoutis, Theoklis; LeMair, Anton
Abstract : Supplemental Digital Content is available in the text.